O uso precoce de bandagens elásticas compressivas “Kinesio taping” em pós-operatório de lipoaspiração - Dias, José Éferson dos Santos (2023)
The search for physical appearance is becoming frequent both among men and women in our country. 2019 statistics from the International Society of Aesthetic Plastic Surgery (ISAPS) show that Brazil has risen to first place in the world in number of aesthetic plastic surgeries. The most frequent are liposuction, breast augmentation and abdominoplasty. But they are not procedures without complications. In this context, dermatofunctional physiotherapy comes to the aid of patient rehabilitation. Being an important tool for protecting the injured tissue and helping the body to induce the healing process, facilitating the manipulation of the recovery time of the operated patient. Kinesio taping (KT) emerged in the 70's and is a physiotherapeutic modality that, through the application of elastic bandages free of latex and with neurological functions, having the same thickness as the skin, supports the muscle and does not restrict movement. Patients with edema after mastectomy for cancer, orthognathic surgeries have shown good results with the use of this lymph technique in the control of pain and edema. The aim of this study is to highlight the presence of complications such as persistent edema, seroma, excessive fibrosis, suture dehiscence and infection in patients admitted to liposuction surgery and/or abdominoplasty. Evidence of the presence of ecchymosis and correlate it with the use of KT, elastic compressive belt and retention plates. Evaluate the patient's pain pattern. A prospective cohort study was carried out that included patients assisted in private physiotherapeutic care in the city of Porto Alegre, Rio Grande do Sul, who underwent liposuction plastic surgery and/or abdominoplasty from January 2019 to December 2022 To measure the ecchymosis, the Image J software was used, where the total body area was measured in a frontal photo and then the areas of ecchymosis were shown. Pain was assessed using the American Pain Society's 11-point corrected numerical verbal scale (0 is no pain and 10 is worst pain). 42 patients were examined and analyzed, all female, with a mean age of 35.81 - 8.09 years. Only 3 (7.1%) were former smokers. 13 (31%) underwent liposuction associated with mastopexy; 11 (26.2%) liposuction and abdominoplasty; 9 (21.4%) liposuction associated with abdominoplasty and mastopexy; and 9 (21.4%) only underwent liposuction. Patients who underwent liposuction associated with mastopexy were younger (32.05 5.93) than patients who underwent liposuction associated with abdominoplasty (41.17 - 8.25) (p=0.022). The median time of use of the KT was 6 days (IQ 6 – 7), for the elastic compressive belt 37.5 days (IQ 30 – 45) and for the retaining plates 37.5 days (IQ 30 – 45). No patient had seroma, hematoma or the development of infection. None had excessive edema and fibrosis that would jeopardize the outcome of the surgery. Only 1 (2.4%) had suture dehiscence (abdominal region). Ecchymosis was observed in 24 (57.1%) of the patients and accounted for a median body area of 14.5% (IQR 8.25 – 25). There was no interpolation between the time of use of the KT and the development of bruises (p=0.659), in the same way with the time of use of the elastic compressive belt (p=0.754) and also of the retaining plates (p=0.836). Pain was reported in 19 (45.2%) of the patients. As for the pain scale used, the median found was 0 (0 – 3.25). KT is a method that presented excellent results with a single rare observation, and there was no development of ecchymosis that compromised a large body surface area.